India-Afghanistan relations in Taliban 2.0: geopolitical shifts and emerging dimensions - Nasir Ahmad Ganaie (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This paper conducts a comprehensive analysis of India’s Afghan foreign policy changes during 2021 after the Taliban takeover. For two decades India has been actively engaged with Afghanistan by investing heavily in infrastructure improvements as well as security developments and governance schemes. Prime Minister Narendra Modi asserts that India switched from supporting the Afghan government to adopting a more realistic stance towards the Taliban administration. This research seeks to advance these shifts while investigating elements that focus on security worries and diplomatic methods together with regional military forces. This study examines how regional stability, together with geopolitical strategies in India, has been altered because of these recent developments. The research follows a qualitative design method which performs systematic analysis of new political developments in India through case studies. This paper analyses the geopolitical transformation factors impacting India through the application of realism, securities theory, and strategic autonomy. India’s diplomatic reactions, security measures, and economic responses to the Taliban takeover between 2021 and the present period make up the paper’s study scope. The paper thoroughly investigates security implications by studying regional architecture security roles between Pakistan and China. India’s complicated foreign policies under Modi become clearer through this paper, which reveals how Indian national security interests, together with regional factors, determine the government’s response to the Taliban’s Taliban’s return to power. The study generates a better comprehension of the current geopolitical frameworks in South Asia.